Parental attitudes regarding interviews about injuries to their children. Issue 1 (1st March 2000) - Scheidt, Peter C; Brenner, Ruth A; Rossi, Maryann W; Clyman, Robert; Boyle, Kerrie E
Abstract : Background —Questions about the circumstances of injuries, especially to infants and young children, might be perceived by parents as threatening or intrusive. Some institutional research review committees express concerns that interviews about childhood injuries may be offensive to parents. The perceived value and potential risk of questions about a young child's injury could affect the quality of responses. Objectives —To assess parents' perceptions of threat and value of interviews about injury to their young children. Setting —District of Columbia, 1 October 1995 to 30 September 1996. Methods —Trained research assistants telephoned the parents of children seen in an emergency department or admitted to the hospital after an injury. To be eligible for inclusion the child must have been <3 years of age and a resident of the District of Columbia at the time of the event. After collection of sociodemographic information and circumstances of injury, the respondents were asked if the interview caused them to feel angry, offended or threatened, and if participation in the study was considered worthwhile. Results —Seventy eight per cent of eligible families were contacted. Among those contacted, 93% completed the interview. Eighty two per cent of respondents were mothers and 11% fathers. Ninety per cent (95% confidence interval (CI) 88.4 to 91.6) of the respondents reported that the interview did not make them feel angry, offended, or threatened. Only 13 (1%; 95% CI 0.5 to 1.5) reported being very angry and 7.1% (95% CI 5.8 to 8.5) reported being a little angry. The majority of participants (61.2%, 95% CI 58.6 to 63.8) felt that participation in the study was definitely worthwhile and only 5.5 % (95% CI 4.3 to 6.7) felt that it was not at all worthwhile. Parents of children with intentional injuries were more likely to report feelings of anger than parents of children with unintentional injuries (24% v 8 %; p=0.02). The per cent of respondents reporting any anger was greater when the interview was conducted within 14 days of the hospital visit compared with later interviews (11% v 7 %; p=0.02). Conclusions —In similar populations most parents of young, injured children are neither upset nor threatened by interviews that probe for details about how their children become injured. In general, collecting data aimed to prevent injuries is perceived as worthwhile, and parents readily cooperate with providing this information. Investigators and review committees should consider that interviews about infant and young child injuries are of no or minimal risk.